Identity formation of non-native English-speaking teachers and prospective teachers through perceptions towards native-speakerism: the Turkish Cypriot story - Akinmulegun, Taye Emmanuel; Kunt, Naciye (Education Assoc South Africa, 2022)
In this article we report on a study in which we used native-speakerism as a lens to investigate the identity formation of nonnative English-speaking teachers and prospective teachers in Northern Cyprus. A qualitative method through narratives was used to access the thoughts and experiences of the participants. In the study the participants' identity formation was revealed by 3 concepts: self-image, self-efficacy, and beliefs about teaching and learning. The findings reveal that the participants had positive and high self-efficacy and self-image with regard to teaching English. Weaknesses often create self-doubt; the participants recognised their weaknesses which propelled them to invest more in themselves. Wheatley (2002) states that teachers' learning and professional growth can be instigated through a level of self-doubt and weaknesses about their abilities. Similarly, their beliefs, a core reflection of their identity, were catalysts to being English language teachers.
Keywords: English-speaking teachers; native-speakerism; non-native English-speaking student teachers; non-native English-speaking teachers; teacher identity